Involvement of small extracellular vesicle-derived TIE-1 in the chemoresistance of ovarian cancer cells. (2021) - Misawa, Tomoka; Toyoshima, Masafumi; Kitatani, Kazuyuki; Ishibashi, Masumi; Hasegawa-Minato, Junko; Shigeta, Shogo; Yaegashi, Nobuo
Highlight: TIE-1 overexpressing ovarian cancer cells were resistant to cisplatin. sEVs-derived TIE-1 decreased chemosensitivity to cisplatin in ovarian cancer cells. DNA damage response caused by cisplatin was suppressed by sEVs-derived TIE-1. Abstract: Background: Ovarian cancer is the most lethal gynecologic malignancy due to the tumor's acquisition of chemoresistance to platinum-based chemotherapy. To solve this problem, we conducted RNAi-based large-scale screening and determined that tyrosine kinase with immunoglobulin-like and EGF-like domains 1 (TIE-1) is a key molecule involved in the platinum resistance of ovarian cancer cells. Recently, a variety of studies have investigated that small extracellular vesicles (sEVs) contribute to the communication between cancer cells, including the development of chemoresistance in ovarian cancer. The purpose of our study is to determine if sEVs-derived TIE-1 is involved in the chemoresistance of ovarian cancer cells. Materials and Methods: TIE-1-overexpressed TOV112D cells, termed TOV112D TIE-1 cells, were established, and sEVs were isolated from TOV112D TIE-1 cells supernatants by ultracentrifugation. We assessed cisplatin sensitivity in recipient cells with TOV112D TIE-1 -derived sEVs by cell-Titer Glo kit. We also asked whether sEV-derived TIE-1 suppressed the DNA damage response in recipient cells and evaluated the DNA damage response by counting cells positive for DNA damage foci. Results: TIE-1 was contained within sEV TIE-1 derived from the cellular supernatant of TOV112D TIE-1 . We showed that sEV-derived TIE-1 decreased chemosensitivity to cisplatin by suppressing the DNA damage response in recipient cells. Conclusion: Our findings suggest that sEV-derived TIE-1 could be a new therapeutic target for refractory ovarian cancer.